Evaluation of residual monomer release after polymerization of different restorative materials used in pediatric dentistry - Duruk, Gülsüm; Akküç, Sibel; Uğur, Yılmaz (BMC oral health, 2022)
The choice of the restorative resin material to be used in pediatric dentistry is of a great importance due to the cytotoxic effects caused by residual monomers. In this study, it was aimed to investigate the amount of residual monomer released over time from different resin-based restorative materials, which are widely used in pediatric dentistry, by using high performance liquid chromatography with photodiode array detector (HPLC-PDA). The compomers in all colors (Twinky Star and Glasiositte A ), two composites with different hybrid properties (Arabesk-GrandioSO), and RMGIC (Ionolux) samples with 2 × 5 mm diameters were prepared. The samples were polymerized with an LED light unit (CELALUX 2, VOCO, Cuxhaven, Germany) and then finishing-polishing procedures were applied. A total of 156 samples were obtained, 13 samples in each of the 12 groups. The amount of residual monomer (BIS-GMA; HEMA, TEGDMA, UDMA) (µg/mL) released into the 75% ethanol solution was determined at different times, (1st hour, 1st, 7th, 14th, and 21st day) by using HPLC-PDA. The residual monomer release continued on day 21 and BIS-GMA was the most released monomer in all groups. HEMA release showed a maximum increase in all the materials at day 7. The highest amount of residual monomer was detected in the gold-colored compomer. HEMA and BIS-GMA release from RMGIC was less than others in all time frames. The color and composition of resin-based restorative materials affect the amount of residual monomer. Pediatric dentists should prefer gold-colored compomers less than others as a restorative material, especially in deep cavities. More studies are needed about the subject.